1999
DOI: 10.1086/314906
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Human Immunodeficiency Virus RNA Below 40 Copies/mL Is Rarein Untreated Persons Even in the First Years of Infection

Abstract: To clarify the frequency and prognostic significance of a plasma human immunodeficiency virus (HIV) RNA load below the detection threshold during the natural history of infection, an ultrasensitive assay was used to identify persons with low virus loads in a cohort of 111 untreated subjects with a known date of seroconversion. Six persons had HIV RNA loads <40 viral copies (VC)/mL during the first years of HIV infection. The probability of meeting the criteria for long-term nonprogression was higher in these s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 13 publications
1
24
0
Order By: Relevance
“…These patients are characterized by nonprogressive disease, a level of virus in plasma below 50 copies/ml, a lack of readily detectable virus by culture, a lack of autologous virus replication in the SCID-Hu mouse, and strong proliferative responses to HIV antigens. Data from this study as well as previous epidemiologic data (12,22,23,30,33,36) indicate that each of these characteristics is quite rare among patients with slowly progressive or a Flow cytometry values indicated were determined at the time of donation. Levels of virus RNA in plasma were determined using a branched chain DNA (bDNA) assay with a sensitivity in plasma of 500 copies/ml and by real-time RT-PCR with a sensitivity of 10 copies/ml.…”
Section: Although Patients With Normal Cd4supporting
confidence: 53%
See 1 more Smart Citation
“…These patients are characterized by nonprogressive disease, a level of virus in plasma below 50 copies/ml, a lack of readily detectable virus by culture, a lack of autologous virus replication in the SCID-Hu mouse, and strong proliferative responses to HIV antigens. Data from this study as well as previous epidemiologic data (12,22,23,30,33,36) indicate that each of these characteristics is quite rare among patients with slowly progressive or a Flow cytometry values indicated were determined at the time of donation. Levels of virus RNA in plasma were determined using a branched chain DNA (bDNA) assay with a sensitivity in plasma of 500 copies/ml and by real-time RT-PCR with a sensitivity of 10 copies/ml.…”
Section: Although Patients With Normal Cd4supporting
confidence: 53%
“…It now appears clear that a large fraction of patients previously considered long-term nonprogressors (LTNPs) ultimately show a decline of CD4 ϩ -T-cell numbers. Members of a small subpopulation (Ͻ0.8% of HIV-infected individuals) show no signs of progression over a 10-year period (12,22,23,36). Extensive studies have demonstrated strong cellular and humoral HIVdirected responses in LTNPs (2,6,7,15,18,29,31,32).…”
Section: Although Patients With Normal Cd4mentioning
confidence: 99%
“…The PBMC of several of these patients have also shown the ability to restrict autologous or challenge virus replication when engrafted into severe combined immunodeficient animals. Although each of these phenotypes are infrequent in HIV-infected patients (14,16), all are associated in this cohort. The present study provides evidence that such patients are also genotypically distinguished by a very high level association with the HLA B*57 allele.…”
Section: Discussionmentioning
confidence: 71%
“…A small subpopulation of patients (Ͻ0.8% of HIV-infected individuals) show no signs of progression over a 10-year period (14,16). These patients are characterized by stable CD4 ϩ T cell counts and Ͻ50 copies of viral RNA͞ml plasma in the absence of antiretroviral therapy.…”
mentioning
confidence: 99%
“…There exists, however, a rare subset of individuals who have undetectable plasma HIV RNA when tested using conventional assays. These "elite controllers" are exceedingly rare, comprising less than 1% of the HIV-infected population (23,31,36). They are distinct from long-term nonprogressors, who have been classically defined as maintaining a CD4 ϩ Tcell count of Ͼ500 cells/mm 3 over a period of several years; many (although not all) elite controllers maintain stable CD4 ϩ T cells, while only a small subset of long-term nonprogressors have undetectable HIV RNA levels (11).…”
mentioning
confidence: 99%